Representation in sea turtle science: Slow progress towards gender equity and globalization revealed from thirty years of symposium abstracts - Robinson, Nathan J.; Mills, Sophie; St.Andrews, Laura; Sundstrom, Allegra; Thibodeau, Jadyn; Yaney-Keller, Adam; Gatto, Christopher R. (Frontiers in Marine Science, 2022)
Sea turtles are a circumglobal taxon that receive considerable research and conservation attention; however, there is little published information about patterns of representation for people working with these species. To assess long-term trends in gender, geographic, and institutional representation within the sea turtle community, we quantified information from 7041 abstracts presented at the International Sea Turtle Symposium (ISTS) between 1988–2018. We report several key findings. (1) The number of authors per abstract doubled over the study period, suggesting greater acknowledgment of contributing individuals. (2) The proportion of female first and last authors has increased over time and at the end of the study period female first authors were in a slight majority (53%) even though last authors remained predominantly (64%) male. (3) Most researchers were from North America (45%) but representation from other continents has increased over time. (4) It was common for authors from North America (34%) and Europe (42%) to conducted research in other continents. This was far less common (<6%) for authors in Africa, Asia, Central America and the Caribbean, and South America. (5) Most authors (48%) were affiliated with academic institutions. Overall, our results reveal a slow trend toward gender equity and globalization in the sea turtle community. Increasing opportunities for underrepresented groups should therefore remain a key priority. To facilitate this process, we suggest hosting symposiums in underrepresented regions, providing grants for underrepresented individuals, developing opportunities to present abstracts remotely via hybrid events, and promoting gender equity in senior researcher positions.